2016
DOI: 10.5797/jnet.oa.2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Selection of CAS or CEA and Proper Use of Protection Device in the Event of CAS According to Carotid Plaque Characteristics

Abstract: Objective: To assess the selection of carotid endarterectomy (CEA) or carotid artery stenting (CAS) and the choice of embolic protection device (EPD) on the basis of a preoperative magnetic resonance (MR) plaque image such as Sp/Sm (signal intensity ratio of carotid plaque against sternocleidomastoid muscle). Methods:Between August 2011 and August 2015, 180 patients who underwent CEA or CAS at our institution were retrospectively analyzed. CEA was selected when soft plaque was suspected by a plaque image of Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The rate of DWI high-intensity lesions on angiography or after CAS varied from 12.9 to 87.1% among reports. 13 , 14) On the other hand, in a recent systematic review, the rate was 18.1% in CEA cases and 40.5% in CAS cases, being relatively high, 5) and the DWI-positive rate limited to ipsilateral CAS cases was 38.1%. In our study, the DWI-positive rate was relatively low and the incidence of symptomatic stroke was 0.9%, being very low.…”
Section: Discussionmentioning
confidence: 92%
“…The rate of DWI high-intensity lesions on angiography or after CAS varied from 12.9 to 87.1% among reports. 13 , 14) On the other hand, in a recent systematic review, the rate was 18.1% in CEA cases and 40.5% in CAS cases, being relatively high, 5) and the DWI-positive rate limited to ipsilateral CAS cases was 38.1%. In our study, the DWI-positive rate was relatively low and the incidence of symptomatic stroke was 0.9%, being very low.…”
Section: Discussionmentioning
confidence: 92%
“… 3) Sawada et al reported that a Carotid Guardwire PS (Medtronic, Santa Rosa, California, USA) or Mo.Ma Ultra (Medtronic, Minneapolis, Minnesota, USA) was effective at treating plaques suggested to be markedly vulnerable by black-blood MRI. 4) We treated the present patient using Carotid Guardwire PS based on the flow reversal concept of Mo.Ma Ultra (Medtronic, Minneapolis, Minnesota, USA). After occluding the distal internal carotid artery with a Carotid Guardwire PS, the recanalization catheter Penumbra 5MAX ACE68 was navigated coaxially with a Carotid Guardwire PS 300 cm to a site close to the thrombus, and it was aspirated by an aspiration pump.…”
Section: Discussionmentioning
confidence: 99%